Local adjustment with path-dependence: the governance structure shift and spatial responding in Chinese third-front city since 1980s - Luo, Zhendong; Zhu, Biyao (International Planning History Society Proceedings, 2018)
A primary task of Chinese planning historians is to show how Chinese urbanization expresses the complex and changing relationship between a strong central government and market forces. Here is one kind of cities called Third-front city, making a pure sample to understand Chinese modern institutional design and related spatial phenomena. Such cities were first built for war-preparing in remote Midwestern China in 1960s, under compulsory power and planned arrangement from central government, which seems not a sustainable mode by general acknowledgement. Yet those cities have still went through transformation and gained follow-up development. With the perspective of historical institutionalism, we assume there exists the interaction of institutional path dependence and endogenous incremental change. This paper takes one typical of them, Shiyan in Hubei Province for empirical study. From the Socialist planned economy stage (1960s to 1970s) to China’s Reform stage (since 1980s), we mainly explore how government structural change effected the city’s development outcomes as a core institutional factor, especially where planning got involved. We find that the initial institutional system dominated by central government had ensured rapid rise of Third-front city in early stage, while producing path dependence and long-term urban spatial influences. In face of transformation, general environment of modest reformation in China had provided enough buffer space for new institutions; On the other hand, despite path dependence in terms of industry pattern, finance structure, administrative power and so on, new local actors’ seeking for incremental changes within original institutional framework also generated transformative effects.